Is organisational culture a hurdle in online knowledge sharing? A conceptual view. (28th June 2021) - Khan, Imran Ullah; Usoro, Abel; Crowe, Malcolm
In the knowledge economy, sharing the key resource-knowledge - is a key challenge. A virtual community (VC), which is a socio-technological system, is considered as a suitable tool to meet the challenge. However, many issues regarding sharing knowledge through VCs need to be addressed. One of such issues is organisational culture. The paper aims to conceptualise the relationship between knowledge sharing and organisational culture in an online environment like VCs. The research uses the organisational cultural model developed by Khan and Usoro. The model consists of support, coordination, innovation and rules orientations. The research hypothesised that support, coordination and innovation orientations have positive relationships with knowledge sharing in online environments while rules orientation has a negative relationship. The research is a conceptual study and based on literature study. In future studies, data will be collected from VCs to test the model.